Legal Protection of The Providing Wages to Labor Workers by Companies Affected by Bankruptcy - Ahmadin, Ahmadin (JURNAL PENDIDIKAN IPS, 2023)
This research aims to determine the extent to which wages are provided to workers by companies that have gone bankrupt. Companies pay wages to laborers, whether intentionally or not, every laborer always complains that they are not given wages. The Constitution of the Republic of Indonesia states that one of the main objectives is to create a just and prosperous national, state life in order to realize social justice by fulfilling the rights of every citizen to obtain work and a decent living for all Indonesian people. Apart from that, article 28 of the Constitution of the Republic of Indonesia states that every person has the right to recognition, guarantees, protection and fair legal certainty as well as equal treatment before the law. The type of research used is Normative-Empirical research. This means that researchers implement normative legal provisions (Laws) in their actions in every specific legal event that occurs in a society. This research was conducted at a company that had gone bankrupt as the sources were the company's workers. Then the results of his research showed that employment is an inseparable part of national development based on the 1945 Constitution of the Republic of Indonesia. By guaranteeing the basic rights of workers while still paying attention to developments in the national and international business world. In accordance with Article 95 paragraph (4) of Law Number 13 of 2003 concerning Employment, if a company is declared bankrupt or liquidated based on applicable laws and regulations, wages and other rights of workers/laborers are debts whose payment takes priority. So, there is a guarantee that employee rights to wages/severance pay can be fulfilled. Then the author's conclusion is that he believes that the company does not have good intentions in providing wages to workers on the grounds that the company has experienced a financial deficit.